Protection of Personal Data in the Use of Digital ID Cards against Misuse of Data from Cyber Hack - Mia Rizki; Augustin Rina Herawati; Endang Larasati (Borong Newinera Publisher, 2024)
Data misuse from cyber hack in Indonesia is still high, judging from data leakage cases in Indonesia, from January to June 2023 there were 35 cases. Data leaks related to personal data on identity cards totaling 377 million data leaked until 2023, the data is contained on the dark web in the form of NIK, full name, date of birth, birth certificate number, blood type, religion, marital status and so on. Writing using a qualitative descriptive approach, this study uses literature studies, namely data collection techniques by conducting a review study of books, literature, records, and reports related to Digital ID cards and data security. This research also uses a fact approach, a case approach to data misuse by cyber hackers, and a statutory approach. The type of data used is secondary data. There are still many personal data leaks in various factors including human error, malware, system security weaknesses, insider threats, lack of security awareness. The impact of data leaks are fraud and identity theft, threatened privacy, financial fraud, national security threats. There are various alternative recommendations to minimize data leakage, this anticipation can be done by the community, students, and the government. This anticipation is in the form of changing passwords regularly, being careful in using applications or social media that have viruses, avoiding uploading photos of ID cards, conducting cyber security training, community empowerment, bureaucracy forming a special IT department responsible for building virtual protection systems, cooperation with third parties.